Analisa Faktor Yang Mempengaruhi Niat Penggunaan E-Wallet Pada Gen Z - Hesniati Hesniati; Ellen Ellen; Florentina Jasmine; Kelvin Kelvin; Lovis Vernando; Novi Aprillia (Universitas Hamzanwadi, 2023)
The purpose of this research is to find out the correlation between perceived ease of use, perceived usefulness, and social influence to the intention of customers to use mobile payment. The survey was conducted toward Z Generation with basic mobile payment information. The research data was collected using a purposive sampling technique, in which researchers took the Z generation in Batam City with the condition that they had used an e-wallet. The final sample of the research is 187 respondents. The analysis technique used was partial least squares (PLS) to evaluate the relationships of the research model. The results showed that perceived ease of use, perceived usefulness, and social influence have a positive significant influence on people intention in using e-wallet